POVERTY AND FISHERMEN’S SOCIAL CAPITAL AT AENG BATU-BATU VILLAGE NORTH GALESONG DISTRICT TAKALAR REGENCY - Wahyuni, Wahyuni; Rahman, Ratnah (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The research was motivated by the social condition of poor fishing communities in the rich sea. The reality is very paradoxical, on the one hand the sea is a rich natural resource and if it can be managed properly it should be able to make the surrounding communities welfare of social and economic life. But on the other hand it turns out that it can not be felt completely by the fishing community because there are some obstacles that they face even many who live in poverty. Social capital as an adhesive, connector and network owned by the fishing community has a role in solving the problems faced by the problem of poverty. the results of research obtained from observations and interviews showed that the factors that cause fishermen's poverty are technological limitations, low level of education, capital ownership, fishing habits, limited marketing of catches. The government's policy is to provide opportunities for outside investors to invest so that they can open jobs and people at Aeng Batu-Batu Village get employment outside of their jobs as fishermen. Other policies include providing Direct Cash Assistance (BLT), Direct Cash Assistance (BTS) and Family Hope Program (PKH). The social capital owned by the fishing community of Aeng Batu-Batu Village is a kinship and kinship relationship that causes them to have a sense of solidarity and it is easy to help each other, besides there are cultural values that are maintained and implemented in the social life of the community.